Understanding real‐world treatment patterns and clinical outcomes in AL amyloidosis patients diagnosed in Canada: A population‐based cohort study. Issue 4 (5th September 2022) - Jimenez‐Zepeda, Victor H.; Reece, Donna; Rigo, Rodrigo; Gogna, Priyanka; Kong, Shiying; Hu, Xun Yang; Chapani, Parv; Cheung, Winson Y.; Brenner, Darren R.; Plante, Richard; Shi, Kun; Husain, Asad; et al.
Abstract: Amyloid light chain (AL) amyloidosis is a rare and chronic bone marrow disorder. Existing claims data can be used to help understand the real‐world treatment patterns and outcomes of this patient population. Various population‐based administrative databases in Alberta, Canada were queried from 2010 to mid‐2019 to identify cases of AL amyloidosis. Baseline patient and disease characteristics, sequencing of pharmacologic therapies, overall survival, and healthcare resource utilization were evaluated. A total of 215 individuals with AL amyloidosis were included. Among patients diagnosed between 2012 and 2019, 149 (85.1%) initiated first‐line, 67 (38.3%) initiated second‐line, 22 (12.6%) initiated third‐line, and 11 (6.3%) initiated fourth‐line systemic therapy. In the first‐line setting, 99/149 (66.4%) received bortezomib, cyclophosphamide, and dexamethasone (CyBorD) and 21/149 (14.1%) received another bortezomib‐based regimen. Survival from time of diagnosis improved over time, with a median overall survival of 25.8 months (95% CI: 9.8, 57.1) for individuals diagnosed in 2010–2011 versus 52.1 months (95% CI: 25.6, NA) for those diagnosed in 2012–2019. Despite this improvement, the proportion of individuals diagnosed in 2012–2019 who survived beyond five‐years remained low (5‐year survival: 48.4%; 95% CI: 40.9, 57.2) which highlights an unmet need for more efficacious therapies.